Human security in a globalised world: concepts and issues for the Muslim world - Hossain, Ishtiaq; Isiaka Abiodun, Adam (Springer, 2015)
This chapter highlights the holistic aspects of human security embracing issues of food, shelter, health, education and work as they relate to the individuals. This chapter is divided into four sections. The first section deals with the fundamentals of human security, its trajectory/historical evolution and conceptual formation. The second section examines the 'Western' components of human security in relation to its applicability. Next, the Islamic/Muslim World perspective of human security is explored in details by drawing on the Qur'an and the Hadith, historical narratives as well as contemporary praxis. The penultimate section highlights some human security challenges as they relate to certain Muslim majority countries to be dealt with in subsequent relevant chapters in this volume.